Performance Analysis of PSO-Based SHEPWM Control of Clone Output Nine-Switch Inverter for Nonlinear Loads - Nirmala Muthusamy; Beena Stanislaus Arputharaj; Vijayanandh Raja (Elektronika ir Elektrotechnika, 2024)
A comprehensive mathematical model of the inverter using nine switches is derived and its carrier high-frequency signal-based Pulse Width Modulation (PWM) is developed for the control of dual nonlinear loads. The Carrier-Based Pulse Width Modulation (CBPWM) provides excellent quality output to linear loads, and it provides high value of Total Harmonic Distortion (THD) for the nonlinear load, where the 5th, 7th, 11th, 13th, and 17th harmonics are highly manifest. Particle Swarm Optimisation (PSO) constructed Selective Harmonic Elimination Pulse Width Modulation (SHEPWM) scheme is proposed to eliminate a higher number of harmonic components and enhance the harmonic profile with reduced number of active semiconductor switches in Nine-Switch Inverter (NSI) control of nonlinear load. The PSO algorithm is proposed to adjust the triggering angles of the SHEPWM scheme and eliminate the targeted harmonics. The main concern associated with the proposed technique is the degree of freedom to lower the harmonics when operated over a comprehensive scale of Modulation Index (MI). To prove the usefulness of the proposed carrier-based PWM, PSO-based SHEPWM technique for NSI, MATLAB-SIMULINK is used to perform the simulations. The experimental prototype of the NSI topology is developed using an ATmega162 microcontroller. The experimental results and its Fast Fourier Transform (FFT) spectrum are over a broad scale of MI, revealing the expertise and efficacy of the proposed control scheme.